100 things you should know about Birds - Johnson, Jinny; Miles Kelly Publishing; Parker, Steve (Miles Kelly Publishing Limited: Essex, 2004)
Here the world of birds has been brought to life using exactly 100 facts and detailed artwork recreating bird habitats and lifestyles. There are also fun activities, such as projects and quizzes, to keep the reader absorbed.
Keywords: Birds